(untitled) (Praxis Educativa, 2016)
Taking into consideration the gap between the explosive growth of enrollment of new students and the small number of graduates, this paper explores the processes of attrition and slowing that increase the distance between theoretical duration and real duration of university courses. Taking as an object of analysis the behavior of students in the University Technical Degree in Cultural Management, -Faculty of Architecture, Planning and Design, UNMDP, we have made a cut on the Cohort 2009 to explore the current dynamics, among the factors that enhance the low rate of graduation, persistence or prolongation of studies and the attrition process of students in the institution.